Analysis of Marinated Flavor Evaluation of Different Parts of Cherry Valley Duck Meat - Ren, Mengting; Li, Wenjing; Zhu, He; Li, Yujie; Ma, Jinlin (International Journal of Agriculture and Food Sciences Research, 2026)
To screen the suitable raw material parts of cherry valley duck for the same brine formula in brined duck products, this study took duck wings, duck necks, duck gizzards, duck heads and duck clavicles as research objects. Volatile components were analyzed by sensory evaluation, solid phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) and gas chromatography-ion mobility spectrometry (GC-IMS). The results showed that duck neck had the best sensory evaluation. A total of 54 volatile compounds were identified in five brined duck parts by SPME-GC-MS, while 22 volatile compounds were detected by GC-IMS. Fourteen key volatile compounds were screened out by relative odor activity value (ROAV) and variable importance in projection (VIP). Among them, 1-Nonanal were the key compounds leading to the differences between brined duck neck and other parts, and brined duck neck exhibited more prominent fatty aroma. SPME-GC-MS and GC-IMS showed a synergistic effect, which provided a theoretical basis for the industrial production of brined duck products.